LACK OF FRESHWATER COOLING IN AIR COMPRESSORS ON SHIPS - Abbas Abbas (Indonesian Journal Of Maritime Review, 2023)
The aim of this research is to find out the factors causing the drop in fresh water cooling system pressure on the compressor, to find out the impact of the factor of the drop in fresh water cooling system pressure on the compressor, and to find out the lack of fresh water cooling in the air compressor on the ship. This research is qualitative research by observing and collecting information from the company. The results of the research show that the impact caused by the decrease in compression pressure on the Main Air Compressor at KM TONASA LINE